2010
DOI: 10.1021/pr901216e
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Enterococcus faecalis V583 Strain and Clinical Isolate V309 under Vancomycin Treatment

Abstract: To understand the molecular mechanisms of bacteria resistance to glycopeptides, we obtained proteomic profiles of vancomycin-resistant Enterococcus faecalis V583 (reference strain) and V309 (clinical isolate) passaged with and without the drug. The specificity and reversibility of vancomycin resistance genes induced in V583 and V309 were further studied over time. By semiquantitative RT-PCR of vancomycin-treated versus untreated samples of both strains, 28 (V583) or 20 (V309) up-regulated proteins, 8 (V583) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…The results are in accordance with previous results of Wang et al [19] that demonstrated that many proteins involved in antibiotic resistance were differentially regulated by vanomycin which also triggered innate signal regulators, adhesion factors, and metabolic gene expression in E. faecalis . Therefore, these responses may enable Enterococcus spp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results are in accordance with previous results of Wang et al [19] that demonstrated that many proteins involved in antibiotic resistance were differentially regulated by vanomycin which also triggered innate signal regulators, adhesion factors, and metabolic gene expression in E. faecalis . Therefore, these responses may enable Enterococcus spp.…”
Section: Discussionsupporting
confidence: 93%
“…Over the past decade numerous genomes of pathogenic bacteria were fully sequenced and annotated, while others are continuously being sequenced and published. More recently to understand the molecular mechanisms of bacteria resistance to glycopeptides, proteomic profiles of vancomycin-resistant Enterococcus faecalis V583 (reference strain) and V309 (clinical isolate) were analysed [19]. Vancomycin induced specifically and reversibly VanA, VanX, VanB, and VanXB.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of differentially expressed proteins within the same strain in different conditions have been performed, shedding light on bacterial adaptation factors to GI tract conditions, such as bile [13-16], acidic pH [18,19], and adhesion to the gut mucosa [20,21]. On the other hand, 2-DE coupled with mass spectrometry (MS) has been used to analyze bacterial protein polymorphisms and to distinguish between closely related pathogenic organisms [22-25], but this approach has rarely been employed to compare strains based on their probiotic features. We previously reported the first study of this kind which highlighted key proteins involved in the adhesion properties of Lactobacillus plantarum to mucin [12].…”
Section: Introductionmentioning
confidence: 99%
“…These studies can elucidate a broader, more generalized, cellular response, but also specialized mechanisms that provide the most difficult to treat bacteria with their ability to survive when others do not. Comparisons of a vancomycin resistant clinical strain and a susceptible reference strain of Enterococcus faecalis showed that while many of the responses to antibiotic treatment were highly similar (suggesting a conserved adaptive responses), a group of specific resistance proteins showed differential abundance in the two strains in the presence or absence of antibiotic (Wang et al 2010). Specifically, VanA and VanX, which are involved in the production of peptidoglycan precursors with decreased glycopeptide-binding affinity (Arthur and Quintiliani 2001), were identified in the resistant strain in the absence of antibiotic, suggesting a prophylactic state of resistance.…”
Section: Bring Out Your Dead: What Susceptible Bacteria Can Teach Us mentioning
confidence: 99%